3G mobile telecommunications interconnection cost model - Yilmaz, Ramazan; Özer, Gökhan; Gungor, Muberra (Bilgesel Yayincilik San & Tic Ltd, 2010)
3G mobile telecommunications interconnection cost model In telecomnumications markets, interconnection fees are significant costs which are incurred by telecommunications operators. Determining cost based interconnection fees is of great importance so as to ensure liberalisation and sustain competition in telecommunications markets. Therefore, Third Generation Interconnection Cost Model aimed to determine cost based interconnection fees for third generation mobile telecommunication networks supporting very high uploading and downloading data transmission, is established within the scope of this study. It is assumed that various releases of UMTS (WCDMA) system can be rolled out by mobile operators in context of this model. Moreover, bottom up long run incremental cost approach is adopted in order to determine unit costs of 3G services.
Keywords: Interconnection Cost; Cost Model; 3G; IMT; UMTS; Bottom Up; Scorched Node; LRIC